تصميم وإنشاء طريق واد المغير في منطقة الحرايق - الخليل - الجعبري, رائد; ادريس, حسام; دوفش, براء (جامعة بوليتكنك فلسطين - كلية الهندسة - مساحة, 2011)
The project is a planning and design of infrastructure for the road connects Intersection of central vegetable market and street bypass line (60), was selected this project to its dynamic, which is a brief to reach the southern region is also working to reduction the traffic on a road test in Southern Region, which is parallel to it in terms of importance and the region, the project consists of two parts: field and office work. This project contains several chapters show field and office work, which has been done on the basis of the project, and contains as well as the appendix show surveying works carried out so far, and we would like to make your attention to the way it was designed according to engineering specifications agreed upon. المشروع عبارة عن تخطيط وتصميم بنية تحتية للطريق الواصل بين مفترق سوق الخضار المركزي والشارع الالتفافي خط رقم (60)، وقد تم اختيار هذا المشروع لموقعه الحيوي الذي يعتبر طريق مختصر للوصول الى المنطقة الجنوبية كما يعمل على تخفيف حركة المرور الواقع على طريق الفحص بالمنطقة الجنوبية الذي يعتبر موازي له من حيث الاهمية والمنطقة ، ويتكون المشروع من جزئين: عمل ميداني وعمل مكتبي . يحتوي هذا المشروع على عدة فصول تبين الأعمال الميدانية والمكتبية التي تم انجاز المشروع على أساسها, ويحتوي كذلك على ملحقات تبين الأعمال المساحية التي تمت , ونود أن نلفت الانتباه إلى انه تم تصميم الطريق حسب المواصفات الهندسية المتفق عليها .
no of pages 178, 12719, مساحة 4/2011 , in the store
Keywords: الطرق - تأهيل